THE USE OF PRESENTATION SOFTWARE IN TEACHING ENGLISH SPEAKING SKILL - Vini Agustina Rohman (Journal of English Education Program (JEEP), 2017)
In recent years, the use of presentation software in classroom instruction has significantly increased globally. The purpose of this study was to find out the teacher’s way of using presentation software in teaching English speaking skill, the teacher’s reason for using presentation software to teach English speaking skill, and the students’ perception teaching learning English speaking skill through presentation software. The sample in this study were an English teacher in Junior High School and 30 eighth grade students of that school. The study was conducted in a cyclic process starting from classroom observation, interview to the teacher, and questionnaire for the students. The study employed a qualitative research design, embracing characteristic of a case study. The results showed that teacher used presentation software by using Laptop and LCD projector. In addition, she included several media in her slide such as pictures, songs, audios, and script dialogue. Moreover, data from interview showed that the teacher’s reasons for using presentation software in teaching English because presentation software provided many advantages for her. Furthermore, the data from questionnaire showed that students’ perception teaching learning English speaking skill by using presentation software were agree. Teaching  learning English speaking skill through presentation aspects which has been rated good is  “Saya suka jika guru mengajar speaking  menggunakan presentation software” (80.00%, 24 students). Almost students choose agree rather than strongly agree because as the teacher said in interview that teaching learning English speaking skill through presentation software was not something new for them. Thus, there were less of students who choose a neutral and no students choose disagree or strongly disagree. This study concludes that the use of presentations software can be implemented in the teaching learning English speaking skill.